2017
DOI: 10.1103/physrevlett.119.058002
|View full text |Cite
|
Sign up to set email alerts
|

Collective Behavior of Chiral Active Matter: Pattern Formation and Enhanced Flocking

Abstract: We generalize the Vicsek model to describe the collective behaviour of polar circle swimmers with local alignment interactions. While the phase transition leading to collective motion in 2D (flocking) occurs at the same interaction to noise ratio as for linear swimmers, as we show, circular motion enhances the polarization in the ordered phase (enhanced flocking) and induces secondary instabilities leading to structure formation. Slow rotations promote phase separation whereas fast rotations generate patterns … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
190
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(207 citation statements)
references
References 37 publications
17
190
0
Order By: Relevance
“…[46]. Again, in the overdamped limit (ζ → ∞), the expression (52) reduces to (18). For a constantly accelerated frame R 0 (t) =ê x a 0 t 2 /2, the mean-square displacement is "superballistic" and will grow with a power law for long times ( r(t) − r(0)) 2 a 2 t 4 /4 resulting from the acceleration.…”
Section: Noise Averagesmentioning
confidence: 99%
See 1 more Smart Citation
“…[46]. Again, in the overdamped limit (ζ → ∞), the expression (52) reduces to (18). For a constantly accelerated frame R 0 (t) =ê x a 0 t 2 /2, the mean-square displacement is "superballistic" and will grow with a power law for long times ( r(t) − r(0)) 2 a 2 t 4 /4 resulting from the acceleration.…”
Section: Noise Averagesmentioning
confidence: 99%
“…The latter type of swimmers experiences also a torque which steadily changes the direction of self-propulsion. These chiral swimmers were studied in various environ-ments [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from that, near surfaces bent self-propelled objects tend to follow circular trajectories [42,43]. In modeling approaches, circle swimmers are often realized by simply imposing an effective torque or rotational drive in addition to the self-propulsion mechanism [15,31,35,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the active crowder without dynamic chirality, the chiral one is affected not only by the active force but also by an extra torque, leading to a circular motion in two dimensional space or a helical motion in three dimensional space. It has been found that the chiral feature of active particles can affect significantly the collective dynamics including transport [53][54][55][56], separation [57,58], sorting [59,60], and so on. However, to the best of our knowledge, how the dynamic chirality of active crowders would influence the configuration change of a polymer chain has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%